Transport and Fate of 137Cs Released From Multiple Sources in the North Atlantic and Arctic Oceans - Maderich, Vladimir; Kim, Kyeong Ok; Bezhenar, Roman; Jung, Kyung Tae; Martazinova, Vazira; Brovchenko, Igor (Frontiers in Marine Science, 2021)
The North Atlantic and Arctic oceans, along with the North Pacific, are the main reservoirs of anthropogenic radionuclides introduced in the past 75 years. The POSEIDON-R compartment model was applied to the North Atlantic and Arctic oceans to reconstruct 137Cs contamination in 1945-2020 due to multiple sources: global fallout, exchange flows with other oceans, point-source inputs in the ocean from reprocessing plants and other nuclear facilities, the impact of the Chernobyl accident and secondary contamination resulting from river runoff and redissolution from bottom sediments. The model simulated the marine environment as a system of 3D compartments comprising the water column, bottom sediment, and biota. The dynamic model described the transfer of 137Cs through the pelagic and benthic food chains. The simulation results were validated using the marine database MARIS. The calculated concentrations of 137Cs in the seaweed and nonpiscivorous and piscivorous pelagic fish mostly followed the concentration of 137Cs in water. The concentration in coastal predator fish lagged behind the concentration in water as a result of a diet that includes both pelagic and benthic organisms. The impact of each considered source on the total concentration of 137Cs in nonpiscivorous fish in the regions of interest was analyzed. Whereas the contribution from global fallout dominated in 1960-1970, in 1970-1990, the contribution of 137Cs released from reprocessing plants exceeded the contributions from other sources in almost all considered regions. Secondary contamination due to river runoff was less than 4% of ocean influx. The maximum total inventory of 137Cs in the Arctic Ocean (31122 TBq) was reached in 1988, whereas the corresponding inventory in the bottom sediment was approximately 6% of the total. The general agreement between simulated and observed 137Cs concentrations in water and bottom sediment was confirmed by the estimates of geometric mean and geometric standard deviation, which varied from 0.89 to 1.29 and from 1.22 to 1.87, respectively. The approach used is useful to synthesize measurement and simulation data in areas with observational gaps. For this purpose, 13 representative regions in the North Atlantic and Arctic oceans were selected for monitoring by using the “etalon” method for classification.